The NAv1.7 blocker protoxin II reduces burn injury-induced spinal nociceptive processing - Torres-Pérez, Jose Vicente; Adamek, Pavel; Palecek, Jiri; Vizcaychipi, Marcela; Nagy, Istvan; Varga, Angelika (Journal of molecular medicine, 2018)
Controlling pain in burn-injured patients poses a major clinical challenge. Recent findings suggest that reducing the activity of the voltage-gated sodium channel Nav1.7 in primary sensory neurons could provide improved pain control in burn-injured patients. Here, we report that partial thickness scalding-type burn injury on the rat paw upregulates Nav1.7 expression in primary sensory neurons 3 h following injury. The injury also induces upregulation in phosphorylated cyclic adenosine monophosphate response element-binding protein (p-CREB), a marker for nociceptive activation in primary sensory neurons. The upregulation in p-CREB occurs mainly in Nav1.7-immunopositive neurons and exhibits a peak at 5 min and, following a decline at 30 min, a gradual increase from 1 h post-injury. The Nav1.7 blocker protoxin II (ProTxII) or morphine injected intraperitoneally 15 min before or after the injury significantly reduces burn injury-induced spinal upregulation in phosphorylated serine 10 in histone H3 and phosphorylated extracellular signal-regulated kinase 1/2, which are both markers for spinal nociceptive processing. Further, ProTxII significantly reduces the frequency of spontaneous excitatory post-synaptic currents in spinal dorsal horn neurons following burn injury. Together, these findings indicate that using Nav1.7 blockers should be considered to control pain in burn injury. KEY MESSAGES: • Burn injury upregulates Nav1.7 expression in primary sensory neurons. • Burn injury results in increased activity of Nav1.7-expressing primary sensory neurons. • Inhibiting Nav1.7 by protoxin II reduces spinal nociceptive processing. • Nav1.7 represents a potential target to reduce pain in burn injury.
Keywords: NAV1.7 Voltage-Gated Sodium Channel; Animals; Rats, Wistar; Spinal Cord; Analgesics; Mice, Knockout; myši knockoutované; nervové receptory; mícha; napěťově řízený sodíkový kanál, typ 9; Cyclic AMP Response Element-Binding Protein; blokátory sodíkových kanálů řízených napětím; Rats, Sprague-Dawley; bolest; Sensory Receptor Cells; peptidy; Male; myši inbrední C57BL; potkani Sprague-Dawley; Burns; protein vázající cAMP responzivní element; Voltage-Gated Sodium Channel Blockers; analgetika; Pain; pavoučí jedy; mužské pohlaví; zvířata; Mice, Inbred C57BL; popálení; Peptides; Spider Venoms; potkani Wistar